Visualization Mapping of the Socio-Technical Architecture based on Tongkonan Traditional House - Taufiq Natsir; Bakhrani Rauf; Faisal Syafar; Ahmad Wahidiyat Haedar; Faisal Najamuddin (JOIV : International Journal on Informatics Visualization, 2023)
The socio-technical architecture of constructing a community's traditional house is a zine-qua-non at the locus of developing tourism destinations in several areas worldwide. A socio-technical system is an old approach that is realigned with developing integrated tourism components, especially various tourist attractions based on local cultural treasures. The results of this qualitative research with a phenomenological approach analyze and explain the noumena (meaning) behind the phenomena (facts) regarding socio-technical architecture based on Tongkonan traditional houses in Tana Toraja, Indonesia. The study results found that architectural works are full of symbolic meaning in constructing Tongkonan traditional houses. The crystallization of basic values and value orientation as the noumena (meaning) behind the socio-technical architectural phenomenon of the Tongkonan traditional house that stands upright is because five pillars support it as a representation of 5A (Attractions, Accessibility, Accommodation, Amenity, Ansilarity) as a component of tourism development. The Tongkonan roof model, which at first glance looks like a person praying by raising their hands up or to God, the Creator of the universe, is proof of the basic values and orientation of the socio-cultural and spiritual values of the Toraja people. The image of a rooster, sun, and arrangement of horns mounted on the Tongkonan wall proves the rich treasures of local socio-cultural life (local wisdom, local genius) of the local community as a result of creativity and innovation that sustainably has value.